Assessment and development of the success strategy in the machinery industry : a case study of Hanoi Mechanical Company - Mai Ha Thanh Uyen; Swierczek, F.W.; Truong, Quang; Bechter, Clemens; Government of Switzerland (Bangkok : Asian Institute of Technology, 1997)
Hanoi Mechanical Company (HAMECO) is one of the pioneers in machine tools industry in Vietnam with its principal products ranging from machine tools to industrial equipment. Before 1989, the company enjoyed the Government protection and had no financial difficulties. After the lifting-up of subsidy system, HAMECO had to face the competitive market. The purpose of this research has been to study how HAMECO has prepared itself to face the present challenges to keep up as the leader in the business in Vietnam. The study first considers the general scenario of machinery industries in Vietnam and analyses the company's strengths and weaknesses. It is intended to point out the strategies that has brought considerable success to the company and recommend some strategies that the company should adopt so as to be in the path of greater achievements.
A research submitted in partial fulfillment of the requirements for the degree of Master of Business Administration.
Research Studies Project Report (M.B.A.) - Asian Institute of Technology, 1997
Keywords: Industrial management -- Vietnam -- Hanoi